Indonesian authors’ stances in citing English research article introductions literature in sciences - Suci Miasari; Safnil Arsyad; Arono Arono (EduLite: Journal of English Education, Literature and Culture, 2018)
Authorial stance is an important aspect in academic texts in academic texts such as research articles (RAs); that is to show the attitude of authors toward the information cited in a reference in order to establish an argument. The objective of this research was to investigate the authorial stances in English RA introductions written by Indonesia authors in the field of sciences (i.e. Biology, Physic and Chemistry). This research employed a descriptive qualitative method. Thirty English research article introductions were included in the corpus in this study. The results show that two authorial stances: neutral and positive stances are found in the texts but no critical stance is used in the corpus of this research. Also, four types of authorial stance (i.e., hedges, booster, attitudinal markers, and self- mention) are used in the RA introductions and the devices in each type of authorial stance are nouns, verbs, adverbs, adjectives and modals. Self-mentions found in this research are subjective pronoun, common noun and possessive adjectives. It can be concluded that Indonesian authors in the field of sciences already use similar types of authorial stances in their English RA introductions to those of international authors writing in English.